(untitled) (Journal of Comparative & International Higher Education, 2021)
Due mainly to globalization, knowledge economies, liberalization, and regulation and accountability regimes, higher education institutions are under increasing pressure to demonstrate their relevance and significance to society. European and North American universities have rearticulated their profiles and adopted entrepreneurial and engaged mandates. The extent to which and how African universities are strategically repositioning themselves in that respect remains obscure. Using relevant theoretical frameworks, this study explores emerging modalities of university-society engagements and linkages in Africa through a critical analysis of the current strategic plans of 30 universities from 14 countries. Qualitative and quantitative analyses of the strategic plans reveal that universities have explicitly identified strategies for the production and transfer of knowledge; for creating networks and partnerships; and for engaging varied stakeholders in decision making at various levels. Implications for further research are identified.